Peran Al-Qur’an Terhadap Problematika Polusi Udara - Muchammad Hafish; Reno Aditya Nasa Saputra (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2023)
Air pollution poses a serious challenge faced by large cities, resulting from human activities such as production, motor vehicles, and forest fires. The escalating air pollution becomes a major contributor to climate change and significant health impacts. The Quran, as the primary guide to life in Islamic teachings, provides guidance on human responsibility as stewards of the Earth to care for and preserve the environment. This research employs a literature study method with a qualitative approach to analyze the Quranic perspective on addressing air pollution problems. The Quran emphasizes the role of humans as stewards with significant responsibilities in safeguarding and nurturing the Earth. Relevant verses highlight prohibitions against harming nature, maintaining harmony between humans and nature, and the importance of environmental preservation. Based on data analysis, air pollution can be defined as the presence of harmful substances in the air. Despite the negative impacts of air pollution, awareness of environmental conditions is increasing. The Quran guides the Islamic community to act wisely in addressing air pollution issues by referring to relevant verses. The Quran provides concrete solutions by emphasizing environmental preservation, wise resource usage, and prohibiting greedy behavior. These verses lay the foundation for environmental ethics that can help address air pollution issues. Solutions involve recycling practices, forest development, industrial waste management, the use of renewable energy, clean technology adoption, vehicle emission control, and wise resource usage. This research underscores the relevance of Quranic teachings in responding to environmental issues, particularly air pollution, and contributes to determining practical steps for environmental sustainability.